(untitled) (Revista de Estudos da Linguagem, 2020)
Abstract: From consistent narratives to cutting-edge graphic design, designers have been investing heavily in making their items competitive in the market. Given the high level of interaction between the players and the games they play, it is to be expected that much of how real-life representations are built in our minds will, in one way or another, influence how we interact with virtual reality, impacting on the playability of a game. Studies on the role of metaphors in (video)games are rather recent and much is yet to be investigated. Through simulations of family life and school routine, for example, these games imply human behavior as systematic and goal-oriented. For this study, we selected popular free life simulation games available at a popular App Store for smartphones. When listing the existing metaphors, we noticed a systematic difference: while conceptual metaphors were multimodal, consisting of a combination of verbal and visual information, primary metaphors showed to be intrinsically monomodal, consisting of visual information. In this study, we argue that metaphors in life simulation games start off as text-dominant, but become image-dominant after some time. That is, players rely on both images and verbal cues while learning how to play the games, but after some time they can just look at the symbolic cues for information. We therefore propose that the classification for metaphors in games should be continuous and as dynamic as the game itself, since there seems to be a movement from text-dominant to visual-dominant metaphors throughout the games. Keywords: metaphor; games; simulation; multimodal metaphors; primary metaphors. Resumo: De narrativas consistentes a design gráfico de ponta, designers têm investido em tornar seus produtos atrativos para o mercado. Dado o alto nível de interação entre jogadores e os jogos que usam, é esperado que muitas das representações das quais fazemos uso na vida real influenciem, até certo ponto, o modo como interagimos com a realidade virtual, o que impacta, portanto, sua jogabilidade. Estudos sobre o papel da metáfora em jogos são bastante recentes e muito ainda precisa ser investigado. Jogos de simulações de vida que envolvem relações familiares e rotinas escolares, por exemplo, parecem sugerir que o comportamento humano seja sistemático e orientado a objetivos específicos. Para o presente estudo, selecionamos jogos de simulação de vida populares em uma App Store para smartphones. Ao listar as metáforas encontradas, notamos uma sistemática diferença: enquanto metáforas conceituais eram multimodais (consistindo de combinações entre informações verbais e visuais), metáforas primárias se mostraram intrinsecamente multimodais (consistindo de informações visuais). Neste estudo, defendemos que metáforas em jogos de simulação de vida começam como texto-dominante, mas, à medida que o jogo se desenrola, tornam-se visualmente dominantes. Ou seja, jogadores dependem de ambos os tipos de informação ao aprender a jogar, mas depois de algum tempo, a informação pode ser obtida ao olhar para os símbolos na tela. Por esta razão, propomos que a classificação de metáforas em jogos se dê de forma contínua, ou seja, que seja tão dinâmica como os próprios jogos, uma vez que o movimento de texto-dominante para imagem-dominante parece se fazer presente no decorrer dos jogos. Palavras-chave: metáfora; jogos; simulação; metáfora multimodal; metáforas primárias.